Hadis tentang Haid dan Pengaruh Alat Kontrasepsi Pencegah Kehamilan terhadap Siklus Haid - Annisaa Siti Zuadah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith about menstruation. This research method is a qualitative type through literature study with content analysis. The research discussion includes general views about menstruation, hadith about menstruation, and the effect of contraceptives to prevent pregnancy on the menstrual cycle. This study concludes that menstruation is a natural cycle as a stipulation that has been established for women based on the explanation of the Prophet's hadith, thereby dismissing various discriminatory myths against menstruating women. Indeed, the menstrual cycle is messed up with the use of contraceptives to prevent pregnancy, but the medical world explains that blood that comes out of the end of a woman's uterus due to the use of contraception that exceeds its period is still categorized as menstruation.